A 2D Layered Lanthanide Hydroxide Showing Slow Relaxation of Magnetization – Dy8(OH)20Cl4·6H2O (Eur. J. Inorg. Chem. 29/2013). Issue 29 (1st October 2013) - Monteiro, Bernardo; Pereira, Cláudia C. L.; Coutinho, Joana T.; Pereira, Laura C. J.; Marçalo, Joaquim; Almeida, Manuel
Abstract : The cover picture shows the unit cell of a layered dysprosium hydroxide material, Dy8 (OH)20 Cl4 · 6H8 O, viewed along the b axis (left) and the c axis (right). The SEM image indicates the high crystallinity of the particles. The temperature dependence of the imaginary component of the AC susceptibility ( χ ″ ) under zero DC field and the magnetic field dependence of the magnetization ( M ) are just two indicators that this is the first example of a layered lanthanide compound showing single‐molecule‐magnet (SMM) behavior. This feature adds new potential applications to these materials in molecular spintronics and quantum computing. Details are discussed in the Short Communication by M. Almeida et al. onp. 5059 ff . For more on the story behind the cover research, see theCover Profile .